Magnetic resonance colonography assessment of acute trinitrobenzene sulfonic acid colitis in pre-pubertal rats - Claire Dupont-Lucas (Public Library of Science (PLoS), 2021)
Pre-pubertal murine models of acute colitis are lacking. Magnetic resonance colonography (MRC) is a promising minimally invasive tool to assess colitis. We aimed to: 1/ Adapt a model of acute experimental colitis to pre-pubertal rats and determine whether MRC characteristics correlate with histological inflammation. 2/ Test this model by administering a diet supplemented in transforming growth factor β2 to reverse inflammation. Twenty-four rats were randomized at weaning to one of 3 groups: Trinitrobenzene Sulfonic Acid (TNBS) group (n = 8) fed a standard diet, that received an intra-rectal 60 mg/kg dose of TNBS-ethanol; Control group (n = 8) fed standard diet, that received a dose of intra-rectal PBS; TNBS+MODULEN group (n = 8) that received a dose of TNBS and were exclusively fed MODULEN-IBD® after induction of colitis. One week after induction of colitis, rats were assessed by MRC, colon histopathology and inflammation markers (Interleukin 1β, Tumor necrosis factor α, Nitric Oxide Synthase 2 and Cyclooxygenase 2). TNBS induced typical features of acute colitis on histopathology and MRC (increased colon wall thickness, increased colon intensity on T2-weighted images, target sign, ulcers). Treatment with MODULEN-IBD® did not reduce signs of colitis on MRC. Inflammatory marker expression did not differ among study groups.